THE METHOD OF LEARNING THE QUR'AN ADDRESSES THE INTENSIFICATION OF EMOTIONAL EXCITEMENT IN SCHOOL - Syatria Adymas Pranajaya; Wardatul Ilmiah; Abdul Wahab Syakhrani (Indonesian Journal of Education (INJOE), 2024)
Through the Quran, students have the opportunity to develop better self- awareness, emotional adjustment, motivation, empathy, and social skills. The method of research used is literature by searching for literature sources related to the context of research. The findings of the research show that the quran Hafalan performed by students can also bring other benefits such as moral and spiritual improvement, as well as a deep understanding of the teachings of Islam. However, it is important to consider that the development of emotional intelligence involves a variety of factors, including the environment, education, and personal experience.